'Felek' and its reflections on Turkish folk literate in the world of complaint/appeals - Şimşek, Esma (My University, 2009)
In Turkish culture, different meanings, related or unrelated with each other made of to 'Felek' as a metaphorical term. 'Felek' with meanings such as sky, space, heaven, world, universe, luck, fortune, chance, timeserver, fate, a layer for each planet and etc. has also an important position in folk literature. The understanding of 'Felek' in Turkish folk literature is a little different from other areas. While 'Felek' is an imagination of sky as a nested bowl or port of sky with seven or nine layers in mysticism and in Divan poetry (tent, dome, roof, cupola, castle, cup, pot, bottle, seven seas, dragon with seven heads, mill, cabinet, furnace, shelter, violin, 'cevşen', helmet, dervish, juggler, planet etc.) it is imagined as world, fate, time, sky, Allah or the divinity that determines the destiny in folk literature. In some texts, 'Felek' is presented as an old man or as a hag who determines the fate of people by turning the wheel of fortune, in others it is presented as a relentless Azrail (the angel of death) who makes any kind of badness to people -especially to minstrels and poets - by separating them from their lovers, by sending them to foreign lands, by fighting with them or by taking their lives. In this article, it is analyzed how 'Felek' is considered in folk literature texts through several examples.
Yakinma/yakarişlar dünyasinda felek ve türk halk edebi?yatina yansimalari
Keywords: Complaining about the time; Fate; Felek; Folk literature; World